Manajemen Hotspot Untuk Pelanggan Pada RT/RW NET Evolve - Grasella, Yessy; Rofiq, Muhammad (JURNAL SISTEM KOMPUTER ASIA, 2024)
ABSTRACT In this study before the existence of hotspot management on RT / RW Net Evove for wifi use is still uncontrolled. Given the pandemic situation, many activities are carried out online both for school and for work. For example, at the hours of learning children who are supposed to look for material to learn but in reality children instead play games. This results in ineffective internet use, especially for students who are still in school.of the system can be done on the hotspot to create a hotspot network naming based on its function and then also add configurations to the firewall section. In this test, it is done by testing each. This research solution that can be taken from the problem is to add a system in a microtic where the system will later emit several hotspot networks with different functions. The addition of the system can be done on the hospot to create a network naming hotspot based on its function and then also add configuration to the firewall section. In this test is done by testing each online voucher, all access voucher and sosmed voucher. In the trial conducted showed results that are in accordance with each of these vouchers. So based on the results of testing vouchers can only access some applications in accordance with the voucher used.